Language, Culture and Cognition from Descartes to Lewes - Kaitaro, Timo (Value Inquiry Book Series, 2022)
"This volume describes how the significance of language and culture in forming human cognition has been understood from the mid-sixteenth century to the mid-nineteenth century"--